Active Learning Beyond the Future - Manuel Brito, Sílvio (IntechOpen, 2019)
Active learning is now a form of learning that accompanies the knowledge evolution that challenges the learner to promote it, but also encourages him to investigate and become emotionally involved in the task. The great key to obtaining this behavior successfully depends, therefore, on the subject's involvement and ability to undertake, so that active learning becomes emotional entrepreneurial learning that generates new ideas and new forms of knowledge. From memorization, we move on to inquiry, from questioning to constructive participation, from hypostasis to problem-solving, from generalization to critical thinking. When we look at this book, we see real examples, concrete, and senses, from the most important act of human nature: learning!